Normalization as a mediator of emotion during unemployment. Issue 6 (2nd November 2021) - Houssemand, Claude; Rosato, Valeria; Thill, Steve; Pignault, Anne
ABSTRACT: Meta-analyses indicated detrimental effects on some psychological dimensions from job loss and extended periods of unemployment. This study analyses three phenomena: causes attributed to unemployment; processes for coping with unemployment; and the emotional impact of joblessness. Using an SEM approach, a model is created in which unemployment normalization acts as a mediator between locus of control and emotions. Method: questionnaires from 260 unemployed people in Luxembourg provided data on perceived control, coping, and emotions. Participants who attribute their situation to bad luck, believe more strongly that unemployment is due to external factors beyond their control, and recognize unemployment as being a common occurrence in life. Such cognitive attribution of unemployment has effects on job seekers' emotions. Those who perceive unemployment in a more positive light experience more positive emotions and fewer negative affects. Negative perceptions of unemployment have no effect on the generation of positive emotion, but have an influence on negative affects. Finally, the influence of perceived-control on emotion is not direct, but is mediated by processes of unemployment normalization. Understanding how unemployed people perceive and experience their situations could help them be more effective in their search for new employment.